ANALISIS PROSEDUR DANA KAS KECIL PADA CV ASIH JAYA - Ivtachul Ma’rifah; Fitri Komariyah (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
This study was conducted to determine the procedures for managing petty cash funds at CV Asih Jaya. The procedures carried out by operations managers, finance managers, and admins are explained in the flowchart chart of an accounting information system regarding the management of petty cash funds. This study uses a descriptive research design. Data collection techniques used are interviews, literature study, and participatory observation. The author was directly involved for approximately one month to find out the petty cash fund management procedures carried out by CV Asih Jaya. The results of this study indicate that CV Asih Jaya has carried out petty cash fund management procedures according to accounting standards applicable in Indonesia. This is useful for top management to focus more on thinking about future business development strategies